The Psychological Type Profile of Readers in the Church of England: Clones of the Clergy or Distinctive Voices?. Issue 2 (17th May 2013) - Francis, Leslie J.; Jones, Susan H.; Robbins, Mandy
Abstract The present study employs Jungian psychological type theory to examine the profile of 236 Readers serving in the Church of England (108 males and 128 females) alongside previously published data providing the psychological type profile of clergy serving within the Church of England (626 men and 237 women). The analysis was interpreted to test two competing accounts of Reader ministry: that Reader ministry expresses similar qualities to those reflected in ordained ministry, and that Reader ministry represents a pioneer ministry on the boundaries of the church. Overall the findings demonstrate significant psychological similarities between those exercising Reader ministry and those exercising ordained ministry, suggesting that, in the current generation, Readers tend to present themselves as clones of the clergy rather than as distinctive voices equipped for pioneer ministry or for fresh expressions of church.